Comparative assessment of sarcopenia screening tools for patients with bone tumors: insights for enhanced clinical application - Yu, Jun; Guan, Qiongyao; Chen, Yanyu; Zhou, Lan; Chen, Jian; Zeng, Yingchun (Frontiers in Nutrition, 2025)
BackgroundSarcopenia screening in bone tumor patients is challenging due to limited awareness, complex procedures, and high costs-especially since most research targets older adults, overlooking younger patients in this group. This study aims to compare the screening efficacy of five different tools for sarcopenia, and to identify the most appropriate screening tool for patients with bone tumors.MethodsThe five sarcopenia screening tools assessed were SARC-F, SARC-Calf, SARC-F + EBM, and the Chinese versions of the Mini-Sarcopenia Risk Assessment scales (MSRA-5 and MSRA-7). The 2019 Asia Working Group for Sarcopenia (AWGS) criteria served as the reference standard for sarcopenia screening.ResultsAmong 300 bone tumor patients, 26% were found to have sarcopenia based on AWGS 2019 criteria. The screening tools varied in performance, with SARC-Calf showing the highest sensitivity and MSRA-7 the lowest specificity. Positive and negative predictive values were moderate across tools, with combined screening methods generally improving sensitivity. The highest overall accuracy (AUC) was observed when using a combination of SARC-F, SARC-Calf, and EBM, which provided both high sensitivity and acceptable specificity.ConclusionThe SARC-Calf and SARC-F + EBM tools demonstrated high accuracy in screening sarcopenia among bone tumor patients. The combined use of SARC-F, SARC-Calf, and SARC-F + EBM yielded superior screening performance, making them suitable for preliminary sarcopenia screening in this patient population.